THE INFLUENCE OF DIGITAL QUR’AN-BASED GAME MEDIA ON THE LEARNING MOTIVATION OF SEVENTH GRADE STUDENTS AT MTSN 2 BEKASI CITY - Aisah, Tisha; Soraya, Syarifah (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2025)
In the world of education, especially in learning activities, the continuity and success of the teaching and learning process is not only influenced by intellectual factors alone, but also by non-intellectual factors, one of which is a student's ability to motivate themselves. Motivation is very important in learning activities, because the presence of motivation encourages the spirit of learning and conversely, the lack of motivation will weaken the spirit of learning. Motivation is an absolute requirement in learning; a student who learns without motivation will not succeed maximally. Digital game media provides new stimulus that can increase students' interest to be more active in learning. The use of technology in religious education has a positive impact on students' learning motivation, especially when digital game media is used optimally in the learning process. This research uses a quasi-experiment design, which is a design that uses a control group but cannot function fully to control external variables that may affect the implementation of the experiment. This model is used to test cause-and-effect hypotheses, namely whether there is a significant effect of using Al-Qur'an digital game media on students' learning motivation. Based on the test results in this study using the Wilcoxon test, a p-value (Asymp. Sig. (2-tailed) = 0.000 was obtained. Thus, this p-value is smaller than the 5% alpha level. This can be seen from the increase in the average pre-test and post-test scores in the experimental class by 20.16 points, compared to the control class which only increased by 10.33 points. Based on the calculations above, it can be concluded that Al-Qur'an digital game media has an effect on learning motivation among seventh-grade students at MTsN 02 Bekasi.